Nadzir's Responsibility for the Crime of Embezzlement of Waqf Assets by Other Parties Based on Indonesian Written Law - Faisal Faisal (International Journal Reglement & Society (IJRS), 2020)
Law Number 41 of 2004 Article 11, states that: "Nadzir has the task of administering waqf assets, managing and developing waqf assets in accordance with their objectives, functions and designations, supervising and protecting waqf assets, reporting on the implementation of tasks to the Waqf Board. Indonesia". In Article 1 and Article 2 of the Regulation Government No. 28 of 2004 states that the purpose of waqf property is for the benefit of worship or other public interests in accordance with Islamic teachings. In practice, Nadzir often finds errors or omissions in carrying out his duties and functions as managers and supervisors of waqf assets. The crime of embezzlement of waqf property is not uncommon in Indonesia. For this reason, of course, Nadzir as supervisor and manager must have responsibility for these errors or omissions, responsibility for criminal acts of embezzlement in accordance with the laws and regulations in force in Indonesia. The procedure used to collect data in this study is in the form of documentation, namely the guidelines used in the form of notes or quotes, searching for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. The task of nadzir who has such a large responsibility emphasizes that waqf will not be able to run if nadzir cannot manage it. So it is clear that the functioning or not of the waqf is very dependent on the nadzir as the party who receives the waqf property to be managed and developed properly. Thus it can be said that nadzir as waqf manager must be better prepared in carrying out his duties, so that what the waqif wants can be accomplished. Nadzir in the Waqf Law has a very important position, in addition to being able to manage and develop waqf assets, nadzir can also determine the designation of waqf assets as long as the wakif does not determine it and if the wakif also agrees with the allocation of waqf assets proposed by nadzir. The importance of the position of nadzir in the process of waqf management in Indonesia is as an institution that plays a role in the long-term vision of the institution, so in its development the waqf law mandates that nadzir both institutions and individuals must be listed in the waqf pledge deed.